A competency-based model of the human resource development management of ustadz at salaf boarding school. Issue 5 (8th June 2015) - Uhbiyati, Nur
Abstract : Purpose: – The purpose of this paper is to study the criteria of qualified ustadz and how the salaf boarding school leader ( kyai ) manages the ustadz in order for them to become qualified ustadz. Design/methodology/approach: – This study uses a qualitative research approach. Data were collected by in-depth interview techniques with kyai and mentor as primary source of data, while participants and alumni as secondary ones. The correctness of data from kyai and mentor then were cross-checked against data from participants and alumni. Findings: – This paper gives the following findings: the qualified ustadz is ustadz who has competencies of personal religious, professional religious, social religious, and life skills; while efforts undertaken by kyai are planning, organizing, implementation and evaluation. Originality/value: – The paper contributes to the Islamic educational institution in development management model for ustadz that has some stages, namely: need analysis, planning design, implementation and development evaluation. The proposed model can be used as a reference for leader of traditional Islamic education around the world in order to improve the quality of ustadz .